The age of innocence - Wharton, Edith, 1862-1937 (Penguin twentieth-century classics., 1996)
When the Countess Ellen Olenska returns from Europe, fleeing her brutish husband, her rebellious independence and passionate awareness of life stir the educated sensitivity of Newland Archer, already engaged to be married to her cousin May Welland, "that terrifying product of the social system he belonged to and believed in, the young girl who knew nothing and expected everything." As the consequent drama unfolds, Edith Wharton's sharp ironic wit and Jamesian mastery of form create a disturbingly accurate picture of men and women caught in a society that denies humanity while desperately defending "civilization."